TECHNOLOGY TRANSFER; A PROBLEM OF BUYER-SELLER RELATIONSHIPS. - Indriyo Gitosudarmo (Faculty of Economics and Business, Universitas Gadjah Mada, 1994)
Technology transfer can be considered as a transaction between the two nations in the marketing of technology that needs dyadic motluations for relational exchange. Understanding the process of such exchange relationship between the supplier and receiver is of benefit in the situation that should be improved to encourage a better